A bonding resin, a composite multi-layer resin material, and a preparation method and application thereof

CN122587128APending Publication Date: 2026-08-18YANTAI CMC PLASTIC PACKAGES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610935522.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-26
Publication Date
2026-08-18

AI Technical Summary

Technical Problem

现有技术要么牺牲粘结性能提高再生料用量,要么牺牲环保性使用原生粘结树脂,尚无一种能够同时实现高再生料用量、高粘结力、低气味、低成本的技术方案

Benefits of technology

本发明中的枞酸能够与聚乙烯和马来酸酐接枝,其中马来酸酐的接枝率较低、游离的马来酸酐会导致材料的气味性显著增加,而枞酸由于空间位阻与聚乙烯之间的接枝率大大降低,而本发明中将马来酸酐作为枞酸和聚乙烯之间的桥梁,提高了枞酸的接枝率,同时本发明中的聚乙烯为再生低密度聚乙烯,经过枞酸的改性使再生低密度聚乙烯能够作为粘结树脂,该方案能够忽略再生低密度聚乙烯的低机械性能等,通过加入引发剂等对再生低密度聚乙烯进行改性,引发剂的含量适中,防止过少的引发剂使接枝率降低,也防止过多的引发剂使再生低密度聚乙烯过度降解,导致力学性能下降。本发明还通过制备得到的粘结性树脂作为次内层和次外层,将线性低密度聚乙烯和再生低密度聚乙烯混合,加入相容剂将二者混合,改善二者之间性能相差过大的问题,再继续将乙烯-乙烯醇共聚物作为中间层,粘结性树脂中的枞酸能够提高粘结性树脂与乙烯-乙烯醇共聚物之间的粘结力,从而提高本发明中复合多层树脂材料层间的结合力,同时也降低了材料的气味性、提高了材料的阻隔性、力学性能等,适用于多个领域。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of adhesive resin, composite multilayer resin material and its preparation method and application, belong to the field of plastic synthesis.First by abietic acid and maleic anhydride mixing, then with the regenerated low-density polyethylene mixing, adhesive resin is prepared, and then it is prepared as adhesive layer to obtain composite multilayer resin material.The application uses maleic anhydride as the bridge between abietic acid and polyethylene, improves the grafting rate of abietic acid, and the polyethylene in the application is regenerated low-density polyethylene, which is modified by abietic acid to make the regenerated low-density polyethylene as a bonding resin, and then a composite multilayer resin material is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of plastic synthesis, specifically to an adhesive resin, a composite multilayer resin material, its preparation method, and its application. Background Technology

[0002] Multilayer co-extruded packaging materials are widely used in cosmetics, food, and pharmaceutical industries due to their excellent barrier properties, mechanical properties, and processing performance. To meet the requirements for oxygen and water vapor barrier properties, ethylene-vinyl alcohol copolymer (EVOH) is typically used as the intermediate barrier layer, bonded to a polyethylene (PE) layer via an adhesive layer to create a five-layer co-extruded structure. With increasing efforts to control plastic pollution, using recycled polyethylene (rPE) to replace virgin polyethylene in packaging material production has become an inevitable trend in the industry.

[0003] However, after repeated heat processing, the molecular chains of recycled polyethylene break, the molecular weight decreases, and the mechanical properties and thermal stability significantly decline. When used directly to prepare adhesive layers, the adhesion to EVOH is insufficient, failing to meet the application requirements. To improve the polarity and adhesive properties of recycled polyethylene, it is usually modified by melt grafting with maleic anhydride (MAH). For example, patent application CN120944022A discloses a maleic anhydride-grafted polyethylene and its preparation method, comprising the following raw materials in parts by weight: 100 parts polyethylene resin, 0.1-2 parts maleic anhydride, 0.01-0.5 parts free radical initiator, 0.01-0.5 parts antioxidant, 0.1-2 parts third monomer, 0.01-0.5 parts stabilizer, and 0.01-0.5 parts crosslinking modifier.

[0004] Meanwhile, most existing commercial bonding resins are made by grafting maleic anhydride onto virgin polyethylene, which is expensive and significantly increases the production cost of multilayer co-extruded materials. Bonding resins made from recycled polyethylene, on the other hand, suffer from problems such as delamination and leakage during filling, transportation, and use due to the complex sources of recycled materials, high impurity content, and uneven grafting reaction. Furthermore, increasing the amount of maleic anhydride used to improve adhesion further exacerbates yellowing and odor issues, affecting the product's appearance and user experience.

[0005] With consumers' increasing demand for environmentally friendly packaging, how to increase the amount of recycled polyethylene added to multilayer co-extruded materials while ensuring the material's bonding performance, mechanical properties, and hygiene and safety performance has become a hot topic and challenge in the industry. Existing technologies either sacrifice bonding performance to increase the amount of recycled material or sacrifice environmental friendliness by using virgin bonding resin. There is currently no technical solution that can simultaneously achieve high recycled material content, high bonding strength, low odor, and low cost.

[0006] Therefore, developing an adhesive resin that uses recycled low-density polyethylene as raw material, has a high grafting rate, low odor, and strong adhesion to EVOH, and applying it to multilayer co-extruded materials, while ensuring material performance, to significantly increase the amount of recycled material and reduce production costs, remains an urgent problem to be solved. Summary of the Invention

[0007] To address the above problems, this invention provides an adhesive resin, a composite multilayer resin material, its preparation method, and its application. First, abietic acid and maleic anhydride are mixed, and then mixed with recycled low-density polyethylene to prepare an adhesive resin. This resin is then used as an adhesive layer to prepare a composite multilayer resin material. The material is used in the packaging field, exhibiting good mechanical properties and low odor, and can be applied in multiple fields.

[0008] The present invention provides an adhesive resin, which is composed of recycled low-density polyethylene, maleic anhydride, abietic acid, an initiator, an antioxidant, and a lubricant;

[0009] The adhesive resin has a melt index of 2.0-4.0 g / 10 min at 190℃ and a tensile strength of 12.5-15.0 MPa at 2.16 kg, and an elongation at break of 250-370%. The grafting rate of abietic acid in the adhesive resin is 0.9-1.5%, and the odor grade of the adhesive resin is 3-3.5.

[0010] Furthermore, the components and their contents in the adhesive resin are as follows: The recycled low-density polyethylene: 45-70 parts by weight; The maleic anhydride: 1.2-2.5 parts by weight; The abietic acid: 2-4 parts by weight; The initiator: 0.1-0.2 parts by weight; The antioxidant: 0.2-0.3 parts by weight; The lubricant: 0.2-0.3 parts by weight.

[0011] Furthermore, the recycled low-density polyethylene has a tensile strength of 8-10 MPa, an elongation at break of 240-280%, and a notched cantilever beam impact strength of 3.3-4.1 kJ / m. 2 The melt flow index at 190℃ / 2.16kg is 2.1-3.5g / 10min, and the heat distortion temperature is 78-85℃.

[0012] Furthermore, the initiator is dicumyl peroxide.

[0013] Furthermore, the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.

[0014] Furthermore, the lubricant is polyethylene wax.

[0015] The present invention also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix recycled low-density polyethylene, initiator, antioxidant and lubricant to obtain a mixture; Step 2: Mix maleic anhydride and abietic acid to obtain a mixed modifier; Step 3: Place the mixture and the mixed modifier in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; Step 4: Dry the masterbatch to obtain the adhesive resin.

[0016] Further, in step 1, the mass ratio of the recycled low-density polyethylene, the initiator, the antioxidant, and the lubricant is (45-70):(0.1-0.2):(0.2-0.3):(0.2-0.3).

[0017] Furthermore, the mixing speed in step 1 is 300-500 rpm, and the mixing time is 15-20 min.

[0018] Further, in step 2, the mass ratio of maleic anhydride, abietic acid and recycled low-density polyethylene is (1.2-2.5):(2-4):(45-70).

[0019] Furthermore, in step 2, the mixing speed is 300-500 rpm, and the mixing time is 15-20 min.

[0020] Furthermore, the screw speed of the twin-screw extruder in step 3 is 250-300 rpm.

[0021] Furthermore, the length-to-diameter ratio of the twin-screw extruder in step 3 is 48:1.

[0022] Furthermore, the feeding speed of the twin-screw extruder in step 3 is 15-20 kg / h.

[0023] Furthermore, the processing temperature of the twin-screw extruder in step 3 is 140-180℃.

[0024] Furthermore, the twin-screw extruder is divided into 10 temperature zones, wherein the temperature of the first temperature zone is 140-150℃, the temperature of the second temperature zone is 150-160℃, the temperature of the third temperature zone is 160-170℃, the temperature of the fourth temperature zone is 160-170℃, the temperature of the fifth temperature zone is 170-180℃, the temperature of the sixth temperature zone is 170-180℃, the temperature of the seventh temperature zone is 170-180℃, the temperature of the eighth temperature zone is 170-180℃, the temperature of the ninth temperature zone is 160-170℃, and the temperature of the tenth temperature zone is 150-160℃.

[0025] Furthermore, the vacuum degree of the twin-screw extruder in step 3 is -0.08 to -0.09 MPa.

[0026] Furthermore, in step 3, the vacuum zone of the twin-screw extruder is located in the eighth temperature zone.

[0027] Furthermore, in step 3, the mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, and the mixed modifier is fed into the side feed port of the fifth temperature zone.

[0028] Furthermore, the drying temperature in step 4 is 50-60℃, and the drying time is 2-3 hours.

[0029] The present invention also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, an intermediate layer, a second outer layer, and an outer layer from the inside out. The intermediate layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has a melt flow index of 4.4-4.8 g / 10 min at 190℃ and a yield of 2.16 kg, a tensile strength of 18-23 MPa, an elongation at break of 350-410%, and a notched cantilever beam impact strength of 5.90-6.50 kJ / m. 2 Its density is 0.90-0.95 g / cm³. 3 The enthalpy of melting / enthalpy of crystallization is (110-115 J / g) / (120-130 J / g); The composite multilayer resin material has a heat distortion temperature of 90-105℃, a biodegradability rate of 27-30%, and an odor level of 3-4. The oxygen barrier properties of the composite multilayer resin material are 0.01-0.04 cm. 3 / pkg•24h, water vapor barrier is 0.10-0.20%, ethanol permeability is 0.10-0.25%.

[0030] Furthermore, the components and their contents in the composite multilayer resin material are as follows: Inner layer: 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch; Inner layer: 40-50 parts by weight of the adhesive resin described above; Intermediate layer: 30-40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 40-50 parts by weight of the adhesive resin described above; Outer layer: 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch.

[0031] Furthermore, the compatibilizer is maleic anhydride-grafted low-density polyethylene.

[0032] The present invention also provides a method for preparing the aforementioned composite multilayer resin material, comprising the following steps: The inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material.

[0033] Furthermore, the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0034] Further, the inner layer comprises 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch.

[0035] Furthermore, the inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, wherein the temperature of the first temperature zone is 140℃, the temperature of the second temperature zone is 150℃, the temperature of the third temperature zone is 160℃, the temperature of the fourth temperature zone is 170℃, the temperature of the fifth temperature zone is 180℃, the temperature of the sixth temperature zone is 180℃, and the screw speed is 4.5 rpm.

[0036] Furthermore, the innermost layer comprises 40-50 parts by weight of the adhesive resin.

[0037] Furthermore, the extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, wherein the temperature of the first temperature zone is 160℃, the temperature of the second temperature zone is 180℃, the temperature of the third temperature zone is 185℃, the temperature of the fourth temperature zone is 190℃, and the screw speed is 17 rpm.

[0038] Furthermore, the intermediate layer comprises 30-40 parts by weight of ethylene-vinyl alcohol copolymer.

[0039] Furthermore, the extrusion temperature of the intermediate layer is 180-200℃, divided into 5 temperature zones, wherein the temperature of the first temperature zone is 180℃, the temperature of the second temperature zone is 190℃, the temperature of the third temperature zone is 195℃, the temperature of the fourth temperature zone is 200℃, the temperature of the fifth temperature zone is 190℃, and the screw speed is 15 rpm.

[0040] Furthermore, the outermost layer comprises 40-50 parts by weight of the adhesive resin.

[0041] Furthermore, the extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, wherein the temperature of the first temperature zone is 140℃, the temperature of the second temperature zone is 150℃, the temperature of the third temperature zone is 160℃, the temperature of the fourth temperature zone is 150℃, and the screw speed is 17rpm.

[0042] Further, the outer layer comprises 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch.

[0043] Furthermore, the outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, wherein the temperature of the first temperature zone is 160℃, the temperature of the second temperature zone is 170℃, the temperature of the third temperature zone is 180℃, the temperature of the fourth temperature zone is 180℃, the temperature of the fifth temperature zone is 185℃, the temperature of the sixth temperature zone is 195℃, and the screw speed is 6.5 rpm.

[0044] Furthermore, the compatibilizer is maleic anhydride-grafted low-density polyethylene.

[0045] The present invention also provides a packaging material comprising the aforementioned composite multilayer resin material.

[0046] The beneficial effects of this invention are: The abietic acid in this invention can be grafted onto polyethylene and maleic anhydride. Maleic anhydride has a low grafting rate, and free maleic anhydride significantly increases the odor of the material. Abietic acid, due to steric hindrance, has a significantly reduced grafting rate with polyethylene. This invention uses maleic anhydride as a bridge between abietic acid and polyethylene, improving the grafting rate of abietic acid. Furthermore, the polyethylene in this invention is recycled low-density polyethylene. Modification with abietic acid enables the recycled low-density polyethylene to be used as a bonding resin. This approach ignores the low mechanical properties of recycled low-density polyethylene. Modification of the recycled low-density polyethylene is achieved by adding initiators, with a moderate initiator content. Insufficient initiator prevents a decrease in grafting rate, while excessive initiator prevents over-degradation of the recycled low-density polyethylene, which would lead to a decline in mechanical properties. This invention also uses the prepared adhesive resin as the inner and outer layers, mixes linear low-density polyethylene and recycled low-density polyethylene, adds a compatibilizer to mix the two, and improves the problem of excessive difference in performance between the two. Then, ethylene-vinyl alcohol copolymer is used as the intermediate layer. The abietic acid in the adhesive resin can improve the adhesion between the adhesive resin and the ethylene-vinyl alcohol copolymer, thereby improving the bonding force between the layers of the composite multilayer resin material in this invention. At the same time, it also reduces the odor of the material, improves the barrier properties and mechanical properties of the material, and is applicable to multiple fields. Detailed Implementation

[0047] The invention will be described in detail below with reference to the embodiments: This invention provides an adhesive resin, a composite multilayer resin material, its preparation method, and its application. First, an adhesive resin is prepared by mixing abietic acid and maleic anhydride with recycled low-density polyethylene. Then, the adhesive resin is used as an adhesive layer to prepare a composite multilayer resin material. The material is used in the packaging field and has good mechanical properties and low odor, making it applicable to multiple fields.

[0048] Example 1 This embodiment provides an adhesive resin, which is composed of recycled low-density polyethylene, maleic anhydride, abietic acid, an initiator, an antioxidant, and a lubricant; The adhesive resin has a melt flow index of 2.5 g / 10 min at 190°C and a tensile strength of 12.7 MPa at 2.16 kg, and an elongation at break of 255%. The grafting rate of abietic acid in the adhesive resin is 0.9%, and the odor rating of the adhesive resin is 3.

[0049] The components and their contents in the adhesive resin described in this embodiment are as follows: The recycled low-density polyethylene: 45 parts by weight; The maleic anhydride: 1.2 parts by weight; The abietic acid: 2 parts by weight; The initiator: 0.1 parts by weight, wherein the initiator is dicumyl peroxide; The antioxidant: 0.2 parts by weight, wherein the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; The lubricant: 0.2 parts by weight, the lubricant is polyethylene wax.

[0050] This embodiment also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix the above-mentioned recycled low-density polyethylene, initiator, antioxidant and lubricant at 300 rpm for 20 min to obtain a mixture; Step 2: Mix the above maleic anhydride and abietic acid at 300 rpm for 20 min to obtain a mixed modifier; Step 3: Place the mixture and the mixed modifier in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; The twin-screw extruder has a screw speed of 300 rpm, a length-to-diameter ratio of 48:1, a feeding speed of 15 kg / h, and a vacuum degree of -0.08 MPa. The twin-screw extruder has a processing temperature of 140-180℃, divided into 10 temperature zones. The temperatures of the first temperature zone are 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, the fourth temperature zone is 170℃, the fifth temperature zone is 180℃, the sixth temperature zone is 180℃, the seventh temperature zone is 180℃, the eighth temperature zone is 180℃, the ninth temperature zone is 170℃, and the tenth temperature zone is 160℃. The mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, the mixed modifier is fed into the side feed port of the fifth temperature zone, and the vacuum zone is located in the eighth temperature zone; Step 4: Dry the masterbatch at 60°C for 3 hours to obtain the adhesive resin.

[0051] This embodiment also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, a middle layer, a second outer layer, and an outer layer from the inside out. The middle layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has the following properties at 190°C: melt flow index of 4.43 g / 10 min (2.16 kg); tensile strength of 18.5 MPa; elongation at break of 351%; and notched impact strength of 5.94 kJ / m². 2 The density is 0.91 g / cm³ 3The enthalpy of fusion / enthalpy of crystallization is 110.97 J / g / 128.29 J / g; The composite multilayer resin material has a heat distortion temperature of 93℃, a biodegradability rate of 28%, and an odor rating of 3.5. The oxygen barrier properties of the composite multilayer resin material are 0.016 cm. 3 / pkg•24h, water vapor barrier is 0.12%, ethanol permeability is 0.14%.

[0052] The components and their contents in the composite multilayer resin material described in this embodiment are as follows: Inner layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Sub-inner layer: 45 parts by weight of the adhesive resin described above; Intermediate layer: 40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 45 parts by weight of the adhesive resin described above; Outer layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0053] This embodiment also provides a method for preparing the composite multilayer resin material, including the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into four temperature zones: the first temperature zone is 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, and the fourth temperature zone is 150℃, with a screw speed of 17 rpm. The lower extrusion temperature of the secondary outer layer is used to avoid uneven interlayer flow caused by excessive temperature difference with the outer polyethylene melt, while ensuring that the active groups of the bonding resin are not destroyed by high temperature. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The composite multilayer resin material has a thickness of 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32. The weight parts of each of the above-mentioned components are the feeding ratio, and the interlayer mass ratio of 48:6:8:6:32 is finally achieved by controlling the flow rate of the multilayer co-extrusion die head.

[0054] Example 2 This embodiment provides an adhesive resin, which is composed of recycled low-density polyethylene, maleic anhydride, abietic acid, an initiator, an antioxidant, and a lubricant; The adhesive resin has a melt index of 3.1 g / 10 min at 190°C and a tensile strength of 14.5 MPa at 2.16 kg, and an elongation at break of 320%. The grafting rate of abietic acid in the adhesive resin is 1.2%, and the odor rating of the adhesive resin is 3.

[0055] The components and their contents in the adhesive resin described in this embodiment are as follows: The recycled low-density polyethylene: 60 parts by weight; The maleic anhydride: 2 parts by weight; The abietic acid: 3 parts by weight; The initiator: 0.15 parts by weight, wherein the initiator is dicumyl peroxide; The antioxidant: 0.2 parts by weight, wherein the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; The lubricant: 0.2 parts by weight, the lubricant is polyethylene wax.

[0056] This embodiment also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix the above-mentioned recycled low-density polyethylene, initiator, antioxidant and lubricant at 400 rpm for 18 min to obtain a mixture; Step 2: Mix the above maleic anhydride and abietic acid at 400 rpm for 18 min to obtain a mixed modifier; Step 3: Place the mixture and the mixed modifier in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; The twin-screw extruder has a screw speed of 300 rpm, a length-to-diameter ratio of 48:1, a feeding speed of 20 kg / h, and a vacuum degree of -0.09 MPa. The twin-screw extruder has a processing temperature of 140-180℃, divided into 10 temperature zones. The temperatures of the first temperature zone are 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, the fourth temperature zone is 170℃, the fifth temperature zone is 180℃, the sixth temperature zone is 180℃, the seventh temperature zone is 180℃, the eighth temperature zone is 180℃, the ninth temperature zone is 170℃, and the tenth temperature zone is 160℃. The mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, the mixed modifier is fed into the side feed port of the fifth temperature zone, and the vacuum zone is located in the eighth temperature zone; Step 4: Dry the masterbatch at 50°C for 3 hours to obtain the adhesive resin.

[0057] This embodiment also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, a middle layer, a second outer layer, and an outer layer from the inside out. The middle layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material, at 190℃, has a melt flow index of 4.72 g / 10 min at 2.16 kg, a tensile strength of 22.9 MPa, an elongation at break of 399%, and a notched cantilever beam impact strength of 6.48 kJ / m. 2 The density is 0.94 g / cm³. 3 The enthalpy of fusion / enthalpy of crystallization is 112 J / g / 120.55 J / g; The composite multilayer resin material has a heat distortion temperature of 95℃, a biodegradability rate of 29.3%, and an odor rating of 4. The oxygen barrier properties of the composite multilayer resin material are 0.025 cm. 3 / pkg•24h, water vapor barrier is 0.20%, ethanol permeability is 0.21%.

[0058] The components and their contents in the composite multilayer resin material described in this embodiment are as follows: Inner layer: 90 parts by weight of the linear low-density polyethylene, 30 parts by weight of the recycled low-density polyethylene, 3 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Sub-inner layer: 40 parts by weight of the adhesive resin described above; Intermediate layer: 35 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 40 parts by weight of the adhesive resin described above; Outer layer: 90 parts by weight of the linear low-density polyethylene, 30 parts by weight of the recycled low-density polyethylene, 3 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0059] This embodiment also provides a method for preparing the composite multilayer resin material, including the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, and the fourth temperature zone at 150℃, and the screw speed at 17 rpm. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The thickness of the composite multilayer resin material is 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0060] Example 3 This embodiment provides an adhesive resin, which is composed of recycled low-density polyethylene, maleic anhydride, abietic acid, an initiator, an antioxidant, and a lubricant; The adhesive resin has a melt index of 3.5 g / 10 min at 190°C and a tensile strength of 14.9 MPa at 2.16 kg, and an elongation at break of 364%. The grafting rate of abietic acid in the adhesive resin is 1.4%, and the odor rating of the adhesive resin is 3.5.

[0061] The components and their contents in the adhesive resin described in this embodiment are as follows: The recycled low-density polyethylene: 70 parts by weight; The maleic anhydride: 2.5 parts by weight; The abietic acid: 4 parts by weight; The initiator: 0.2 parts by weight, wherein the initiator is dicumyl peroxide; The antioxidant: 0.3 parts by weight, wherein the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; The lubricant: 0.3 parts by weight, the lubricant is polyethylene wax.

[0062] This embodiment also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix the above-mentioned recycled low-density polyethylene, initiator, antioxidant and lubricant at 500 rpm for 15 min to obtain a mixture; Step 2: Mix the above maleic anhydride and abietic acid at 500 rpm for 15 min to obtain a mixed modifier; Step 3: Place the mixture and the mixed modifier in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; The twin-screw extruder has a screw speed of 250 rpm, a length-to-diameter ratio of 48:1, a feeding speed of 15 kg / h, and a vacuum degree of -0.09 MPa. The twin-screw extruder has a processing temperature of 140-180℃, divided into 10 temperature zones. The temperatures of the first temperature zone are 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, the fourth temperature zone is 170℃, the fifth temperature zone is 180℃, the sixth temperature zone is 180℃, the seventh temperature zone is 180℃, the eighth temperature zone is 180℃, the ninth temperature zone is 170℃, and the tenth temperature zone is 160℃. The mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, the mixed modifier is fed into the side feed port of the fifth temperature zone, and the vacuum zone is located in the eighth temperature zone; Step 4: Dry the masterbatch at 60°C for 2 hours to obtain the adhesive resin.

[0063] This embodiment also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, a middle layer, a second outer layer, and an outer layer from the inside out. The middle layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has the following properties at 190℃: melt flow index of 4.59 g / 10 min (2.16 kg); tensile strength of 20.3 MPa; elongation at break of 408%; and notched impact strength of 6.12 kJ / m². 2 The density is 0.92 g / cm³. 3 The enthalpy of fusion / enthalpy of crystallization is 114.97 J / g / 129.10 J / g; The composite multilayer resin material has a heat distortion temperature of 101℃, a biodegradability rate of 27.1%, and an odor rating of 3.5. The oxygen barrier properties of the composite multilayer resin material are 0.037 cm. 3 / pkg•24h, water vapor barrier is 0.18%, ethanol permeability is 0.15%.

[0064] The components and their contents in the composite multilayer resin material described in this embodiment are as follows: Inner layer: 100 parts by weight of the linear low-density polyethylene, 35 parts by weight of the recycled low-density polyethylene, 3 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Inner layer: 50 parts by weight of the adhesive resin described above; Intermediate layer: 30 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 50 parts by weight of the adhesive resin described above; Outer layer: 100 parts by weight of the linear low-density polyethylene, 35 parts by weight of the recycled low-density polyethylene, 3 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0065] This embodiment also provides a method for preparing the composite multilayer resin material, including the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, and the fourth temperature zone at 150℃, and the screw speed at 17 rpm. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The thickness of the composite multilayer resin material is 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0066] Comparative Example 1 This comparative example provides an adhesive resin composed of recycled low-density polyethylene, maleic anhydride, initiator, antioxidant and lubricant; The adhesive resin has a melt index of 2.7 g / 10 min at 190°C and a tensile strength of 10.2 MPa at 2.16 kg, and an elongation at break of 220%. The odor rating of the adhesive resin is 4.

[0067] The components and their contents in the adhesive resin described in this comparative example are as follows: The recycled low-density polyethylene: 45 parts by weight; The maleic anhydride: 1.2 parts by weight; The initiator: 0.1 parts by weight, wherein the initiator is dicumyl peroxide; The antioxidant: 0.2 parts by weight, wherein the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; The lubricant: 0.2 parts by weight, the lubricant is polyethylene wax.

[0068] This comparative example also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix the above-mentioned recycled low-density polyethylene, initiator, antioxidant and lubricant at 300 rpm for 20 min to obtain a mixture; Step 2: Place the mixture and maleic anhydride in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; The twin-screw extruder has a screw speed of 300 rpm, a length-to-diameter ratio of 48:1, a feeding speed of 15 kg / h, and a vacuum degree of -0.08 MPa. The twin-screw extruder has a processing temperature of 140-180℃, divided into 10 temperature zones. The temperatures of the first temperature zone are 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, the fourth temperature zone is 170℃, the fifth temperature zone is 180℃, the sixth temperature zone is 180℃, the seventh temperature zone is 180℃, the eighth temperature zone is 180℃, the ninth temperature zone is 170℃, and the tenth temperature zone is 160℃. The mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, the maleic anhydride is fed into the side feed port of the fifth temperature zone, and the vacuum zone is located in the eighth temperature zone; Step 3: Dry the masterbatch at 60°C for 3 hours to obtain the adhesive resin.

[0069] This comparative example also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, an intermediate layer, a second outer layer, and an outer layer from the inside out. The intermediate layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has the following properties at 190℃: melt flow index of 3.92 g / 10 min (2.16 kg); tensile strength of 15.3 MPa; elongation at break of 330%; and notched impact strength of 3.71 kJ / m². 2 The density is 0.93 g / cm³. 3 ; The composite multilayer resin material has a heat distortion temperature of 90℃, a biodegradability rate of 25%, and an odor rating of 4.5. The oxygen barrier property of the composite multilayer resin material is 0.1012 cm⁻¹. 3 / pkg•24h, water vapor barrier is 0.42%, ethanol permeability is 0.25%.

[0070] The components and their contents in the composite multilayer resin material described in this comparative example are as follows: Inner layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Sub-inner layer: 45 parts by weight of the adhesive resin described above; Intermediate layer: 40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 45 parts by weight of the adhesive resin described above; Outer layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0071] This comparative example also provides a method for preparing the aforementioned composite multilayer resin material, comprising the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, and the fourth temperature zone at 150℃, and the screw speed at 17 rpm. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The thickness of the composite multilayer resin material is 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0072] Comparative Example 2 This comparative example provides an adhesive resin composed of recycled low-density polyethylene, abietic acid, an initiator, an antioxidant, and a lubricant; The adhesive resin has a melt index of 2.0 g / 10 min at 190°C and a tensile strength of 11.3 MPa at 2.16 kg, and an elongation at break of 219%. The grafting rate of abietic acid in the adhesive resin is 0.02%, and the odor rating of the adhesive resin is 3.

[0073] The components and their contents in the adhesive resin described in this comparative example are as follows: The recycled low-density polyethylene: 45 parts by weight; The abietic acid: 2 parts by weight; The initiator: 0.1 parts by weight, wherein the initiator is dicumyl peroxide; The antioxidant: 0.2 parts by weight, wherein the antioxidant is antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; The lubricant: 0.2 parts by weight, the lubricant is polyethylene wax.

[0074] This comparative example also provides a method for preparing the adhesive resin, comprising the following steps: Step 1: Mix the above-mentioned recycled low-density polyethylene, initiator, antioxidant and lubricant at 300 rpm for 20 min to obtain a mixture; Step 2: Place the mixture and the abietic acid in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; The twin-screw extruder has a screw speed of 300 rpm, a length-to-diameter ratio of 48:1, a feeding speed of 15 kg / h, and a vacuum degree of -0.08 MPa. The twin-screw extruder has a processing temperature of 140-180℃, divided into 10 temperature zones. The temperatures of the first temperature zone are 140℃, the second temperature zone is 150℃, the third temperature zone is 160℃, the fourth temperature zone is 170℃, the fifth temperature zone is 180℃, the sixth temperature zone is 180℃, the seventh temperature zone is 180℃, the eighth temperature zone is 180℃, the ninth temperature zone is 170℃, and the tenth temperature zone is 160℃. The mixture is fed into the main feed port (first temperature zone) of the twin-screw extruder, the abietic acid is fed into the side feed port of the fifth temperature zone, and the vacuum zone is located in the eighth temperature zone; Step 3: Dry the masterbatch at 60°C for 3 hours to obtain the adhesive resin.

[0075] This comparative example also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, an intermediate layer, a second outer layer, and an outer layer from the inside out. The intermediate layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resin, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has the following properties at 190°C: melt flow index of 3.5 g / 10 min at 2.16 kg; tensile strength of 12.1 MPa; elongation at break of 303%; and notched impact strength of 3.44 kJ / m². 2 The density is 0.95 g / cm³. 3 ; The composite multilayer resin material has a heat distortion temperature of 74°C, a biodegradability rate of 26%, and an odor rating of 3. The oxygen barrier property of the composite multilayer resin material is 0.1711 cm⁻¹. 3 / pkg•24h, water vapor barrier is 0.40%, ethanol permeability is 0.33%.

[0076] The components and their contents in the composite multilayer resin material described in this comparative example are as follows: Inner layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Sub-inner layer: 45 parts by weight of the adhesive resin described above; Intermediate layer: 40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 45 parts by weight of the adhesive resin described above; Outer layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0077] This comparative example also provides a method for preparing the aforementioned composite multilayer resin material, comprising the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, and the fourth temperature zone at 150℃, and the screw speed at 17 rpm. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The thickness of the composite multilayer resin material is 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0078] Comparative Example 3 This comparative example also provides a composite multilayer resin material, which has a five-layer structure, consisting of an inner layer, a second inner layer, an intermediate layer, a second outer layer, and an outer layer from the inside out. The intermediate layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are commercially available adhesive resins, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material, at 190℃, has a melt flow index of 4.21 g / 10 min at 2.16 kg, a tensile strength of 19.4 MPa, an elongation at break of 378%, and a notched cantilever beam impact strength of 5.09 kJ / m. 2 The density is 0.95 g / cm³. 3 ; The composite multilayer resin material has a heat distortion temperature of 90℃, a biodegradability rate of 20%, and an odor rating of 3.5. The oxygen barrier properties of the composite multilayer resin material are 0.0926 cm⁻¹. 3 / pkg•24h, water vapor barrier is 0.42%, ethanol permeability is 0.30%.

[0079] The components and their contents in the composite multilayer resin material described in this comparative example are as follows: Inner layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; Inner layer: 45 parts by weight of commercially available adhesive resin; Intermediate layer: 40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 45 parts by weight of commercially available adhesive resin; Outer layer: 80 parts by weight of the linear low-density polyethylene, 40 parts by weight of the recycled low-density polyethylene, 2 parts by weight of the compatibilizer and 3 parts by weight of the degradation masterbatch; The compatibilizer is maleic anhydride-grafted low-density polyethylene. The degradation masterbatch is graded PE3000.

[0080] This comparative example also provides a method for preparing the aforementioned composite multilayer resin material, comprising the following steps: The above-mentioned inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material; The inner layer extrusion temperature is 140-180℃, divided into 6 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, the fourth temperature zone at 170℃, the fifth temperature zone at 180℃, and the sixth temperature zone at 180℃, and the screw speed at 4.5 rpm. The extrusion temperature of the inner layer is 160-190℃, divided into 4 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 180℃, the third temperature zone at 185℃, and the fourth temperature zone at 190℃, and the screw speed at 17 rpm. The intermediate layer is extruded at a temperature of 180-200℃, divided into 5 temperature zones: the first temperature zone is 180℃, the second temperature zone is 190℃, the third temperature zone is 195℃, the fourth temperature zone is 200℃, and the fifth temperature zone is 190℃. The screw speed is 15 rpm. The extrusion temperature of the secondary outer layer is 140-160℃, divided into 4 temperature zones, with the first temperature zone at 140℃, the second temperature zone at 150℃, the third temperature zone at 160℃, and the fourth temperature zone at 150℃, and the screw speed at 17 rpm. The outer layer extrusion temperature is 160-195℃, divided into 6 temperature zones, with the first temperature zone at 160℃, the second temperature zone at 170℃, the third temperature zone at 180℃, the fourth temperature zone at 180℃, the fifth temperature zone at 185℃, and the sixth temperature zone at 195℃, and the screw speed at 6.5 rpm. The thickness of the composite multilayer resin material is 0.5 mm, and the mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:32.

[0081] Table 1 lists the components and contents of the adhesive resin described in this embodiment and the comparative example.

[0082] Table 2 shows the performance of the adhesive resins described in this embodiment and the comparative example.

[0083] Table 3 shows the components and contents of the composite multilayer resin materials described in this embodiment and the comparative example.

[0084] Table 4 shows the performance of the composite multilayer resin materials described in this embodiment and the comparative example.

[0085] The table above shows the composition and properties of the adhesive resin and composite multilayer resin materials in this embodiment and comparative examples. The adhesive resin prepared by this invention has better compatibility with the inner and outer layers and a higher grafting rate. The barrier properties and mechanical properties of the prepared composite material are better than those of conventional commercial adhesive resin (Comparative Example 3). In Comparative Example 1, after grafting with maleic anhydride, the amount of free maleic anhydride monomer increases, and the odor of the material also increases. In Comparative Example 2, there is no maleic anhydride, only abietic acid, which cannot react due to steric hindrance. The commercial adhesive resin in Comparative Example 3 is not biodegradable and has poor compatibility with the degradation masterbatch, which inhibits the biodegradation activity of the degradation masterbatch. Therefore, the overall biodegradation rate is significantly lower than that of this embodiment.

[0086] The test conditions for water vapor barrier properties in this embodiment and comparative example are as follows: Record the initial weight of the material as W0. After sealing, add purified water to the material until it is 3 / 4 full. Tighten the cap with a torque of 30 N·cm-90 N·cm. Wipe the outer surface clean with a silk cloth. Record the weight of the material at this time as W1. Then place the material in a constant temperature and humidity chamber with a temperature of 40℃±2℃ and a relative humidity of 25%±5% for 14 days. After taking it out, place it at room temperature for 45 minutes and weigh it again. Record the weight of the material at this time as W2. The water vapor barrier property is represented by (W1-W2) / (W1-W0)×100%. The test standard for oxygen barrier properties is ASTM F1307-02. The testing methods and standards for odor rating are VDA 270-2016; The test method and standard for biodegradation rate is GB / T 19277.1-2011, and the test conditions are 58℃±2℃ and relative humidity 55%±5%.

[0087] In this invention, the adhesiveness of the bonding resin in the composite multilayer material is manifested as the barrier properties of the material. Since the material is bonded in a molten state in the multilayer co-extrusion extruder, there is no phenomenon of interlayer separation, so there is no need to test the interlayer bonding performance.

[0088] As can be seen from the above, the adhesive resin and composite multilayer resin material described in this invention have a wide range of applications, low cost, and extremely high market prospects.

[0089] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any other way. Any modifications or equivalent changes made based on the technical essence of the present invention shall still fall within the scope of protection claimed by the present invention.

Claims

1. An adhesive resin, characterized in that, The adhesive resin is composed of recycled low-density polyethylene, maleic anhydride, abietic acid, initiator, antioxidant and lubricant; The adhesive resin has a melt index of 2.0-4.0 g / 10 min at 190℃ and a tensile strength of 12.5-15.0 MPa at 2.16 kg, and an elongation at break of 250-370%. The grafting rate of abietic acid in the adhesive resin is 0.9-1.5%, and the odor grade of the adhesive resin is 3-3.

5.

2. The adhesive resin according to claim 1, characterized in that, The components and their contents in the adhesive resin are as follows: The recycled low-density polyethylene: 45-70 parts by weight; The maleic anhydride: 1.2-2.5 parts by weight; The abietic acid: 2-4 parts by weight; The initiator: 0.1-0.2 parts by weight; The antioxidant: 0.2-0.3 parts by weight; The lubricant: 0.2-0.3 parts by weight.

3. A method for preparing the adhesive resin according to any one of claims 1-2, characterized in that, Includes the following steps: Step 1: Mix recycled low-density polyethylene, initiator, antioxidant and lubricant to obtain a mixture; Step 2: Mix maleic anhydride and abietic acid to obtain a mixed modifier; Step 3: Place the mixture and the mixed modifier in a twin-screw extruder for melt extrusion, cool and pelletize to obtain masterbatch; Step 4: Dry the masterbatch to obtain the adhesive resin.

4. The preparation method according to claim 3, characterized in that, The processing temperature of the twin-screw extruder in step 3 is 140-180℃.

5. The preparation method according to claim 3, characterized in that, In step 3, the mixture is fed into the main feed port of the twin-screw extruder, and the mixed modifier is fed into the side feed port of the fifth temperature zone of the twin-screw extruder.

6. A composite multilayer resin material, characterized in that, The composite multilayer resin material has a five-layer structure, consisting of an inner layer, a second inner layer, a middle layer, a second outer layer, and an outer layer from the inside out. The middle layer is an ethylene-vinyl alcohol copolymer, the second inner layer and the second outer layer are the adhesive resins described in any one of claims 1-2, and the inner layer and the outer layer are composed of linear low-density polyethylene, recycled low-density polyethylene, a compatibilizer, and a degradation masterbatch. The composite multilayer resin material has a melt flow index of 4.4-4.8 g / 10 min at 190℃ and a yield of 2.16 kg, a tensile strength of 18-23 MPa, an elongation at break of 350-410%, and a notched cantilever beam impact strength of 5.90-6.50 kJ / m. 2 Its density is 0.90-0.95 g / cm³. 3 The enthalpy of melting / enthalpy of crystallization is (110-115 J / g) / (120-130 J / g); The composite multilayer resin material has a heat distortion temperature of 90-105℃, a biodegradability rate of 27-30%, and an odor level of 3-4. The oxygen barrier properties of the composite multilayer resin material are 0.01-0.04 cm. 3 / pkg•24h, water vapor barrier is 0.10-0.20%, ethanol permeability is 0.10-0.25%.

7. The composite multilayer resin material according to claim 6, characterized in that, The components and their contents in the composite multilayer resin material are as follows: Inner layer: 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch; Inner layer: 40-50 parts by weight of the adhesive resin described above; Intermediate layer: 30-40 parts by weight of ethylene-vinyl alcohol copolymer; Secondary outer layer: 40-50 parts by weight of the adhesive resin described above; Outer layer: 80-100 parts by weight of the linear low-density polyethylene, 30-40 parts by weight of the recycled low-density polyethylene, 2-3 parts by weight of the compatibilizer and 2-3 parts by weight of the degradation masterbatch.

8. A method for preparing the composite multilayer resin material according to claim 6, characterized in that, Includes the following steps: The inner layer, sub-inner layer, middle layer, sub-outer layer and outer layer components are placed in a multilayer co-extrusion extruder and extruded to obtain the composite multilayer resin material.

9. The preparation method according to claim 8, characterized in that, The mass ratio of the inner layer, the second inner layer, the middle layer, the second outer layer, and the outer layer is 48:6:8:6:

32.

10. A packaging material, characterized in that, The packaging material includes the composite multilayer resin material as described in claim 6.

Citation Information

Patent Citations

  • Preparation method of maleic anhydride grafted polyethylene

    CN120944022A